Una rivoluzione visuale: quando l’Intelligenza Artificiale mette l’arte nelle mani di tutti (Archeomatica, 2024)
In contemporary society, artificial intelligence (AI) impacts human lives to different extents, including reshaping the public's creative experience.Software and programs enable users to create images from scratch, notwithstanding their actual knowledge or competencies.The visual art system is currently facing an ongoing democratization process, in which the distance separating the creator and the informatic algorithm is gradually fading. Therefore, there is a growing need to analyze AI's implications on the creative process.The paper will analyze the different software and websites providing image- generating services while discussing their impact on society as a whole.